The prognostic value of left ventricular systolic function and cardiac biomarkers in pediatric severe sepsis. Issue 13 (March 2019) - Li, Juanzhen; Ning, Botao; Wang, Ying; Li, Biru; Qian, Juan; Ren, Hong; Zhang, Jian; Hu, Xiaowei
Abstract : Abstract: Echocardiography and cardiac biomarkers, such as cardiac troponin I (cTnI) and N-terminal pro-B-type natriuretic peptide (NT-pro BNP) are useful tools to evaluate cardiac dysfunction. Left ventricular systolic dysfunction (LVSD) is common in pediatric severe sepsis. The aim of this study is to evaluate the prognostic value of LVSD, cTnI, and NT-pro BNP for pediatric severe sepsis. A prospective, single center, observational study was conducted. Severe sepsis children were enrolled in the study from December 2015 to December 2016 in pediatric intensive care unit of Shanghai Children's Medical Center. Recorded general information, transthoracic echocardiography were performed at day 1, 2, 3, 7, and 10, using Simpson to measure left ventricular end-diastolic dimension and left ventricular end-systolic dimension, obtained echocardiography parameters: left ventricular ejection fraction (LVEF), left ventricular fractional shortening, left ventricular end-diastolic volume, left ventricular end- systolic volume, stroke volume, cardiac output. At the same time collecting the blood sample to measure cTnI, NT-pro BNP. The definition of LVSD was LVEF <50%. According to the prognosis of 28 days, children with severe sepsis were divided into survived group and nonsurvived group. Total of 50 pediatric patients who were diagnosed with severe sepsis (including septic shock) were enrolled, the incidence of LVSD was 52%. The 28-day mortality rate of severe sepsis was 34%. Multivariate logistic regression analyses for predictors of death in pediatric severe sepsis revealed that the 28-day mortality of severe sepsis was associated with mechanical ventilation (MV) within the first 6 hours of admission (odds ratio [OR], 0.01; 95% confidence interval [CI], 0.00–0.07) and total MV time (OR, 0.81; 95% CI, 0.68–0.97). The receiver operating characteristic curves LVEF (area under curve = 0.526), cTnI (area under curve = 0.480), and NT-pro BNP (area under curve = 0.624) were used to predict the 28-day mortality in pediatric severe sepsis. Follow-up echocardiography parameters for survived group and nonsurvived group showed no significant changes in LVEF, LVFS, stroke volume index, cardiac index (CI), left ventricular end-diastolic volume index and left ventricular end-systolic volume index at day 1, 2, 3, 7, and 10, except for CI at day 1 and 2. Kaplan–Meier plot of 28-day mortality and LVSD in pediatric severe sepsis showed there were no statistical differences ( χ 2  = 0.042, P  = .837). LVSD occurs frequently in pediatric with severe sepsis. The 28-day mortality rate of severe sepsis was also high. In this study, none of LVSD, cTnI, and NT-proBNP was associated with the prognosis of pediatric severe sepsis.